The influence of institutional pressures on the implementation of sustainability risk management in Malaysian palm oil mills - Abdul Razak, Shazrul Ekhmar; Mustapha, Mazlina; Mohammed Shah, Sabarina (Universiti Putra Malaysia, 2025)
Sustainability risk management (SRM) has emerged as an important management control system in recent years and serves as a means to reduce sustainability issues arising as a consequence of a company’s operations. Despite the increasing interest, the implementation of SRM remains scarce, and Malaysia is no exception. This paper aims to provide useful insight by investigating the influence of institutional pressures on the implementation of SRM by Malaysian companies. Drawing on institutional theory, this paper aims to examine the influence of regulatory, competitive, and normative pressures on the implementation of SRM in Malaysian palm oil mills. A survey questionnaire was distributed to 407 managers of palm oil mills across Malaysia between July and December 2020, with a response rate of 28.9%. The data from 118 usable questionnaires were analysed using partial least squares structural equation modelling (PLS-SEM). The findings highlight that regulatory pressure and competitive pressure significantly influence the implementation of SRM. The findings contribute to institutional research by understanding the reasons behind SRM implementation in developing country settings. Practically, the findings provide useful insights for policymakers to initiate the implementation of SRM to address sustainability issues.